From Corporate Narratives to Public Trust: Exploring CSR Communication and Social Impact in Southeast Asia’s Digital Era - Muhammad Nafri Yandi; Mutiara Fatimah; Wilda Junintan; Titi Antin; Yefni Yefni; Darusman Darusman; Ginda Ginda (Jogjakarta Communication Conference (JCC), 2026)
Corporate Social Responsibility (CSR) has increasingly emerged as a pivotal mechanism through which corporations in Southeast Asia build public trust and deliver measurable social impact. In the digital era, the communication of CSR activities through online platforms has transformed the way organizations engage with stakeholders and society at large. This study investigates the relationship between CSR communication strategies, public trust, and social impact among corporations operating in Indonesia and Southeast Asia. Employing a systematic literature; review and qualitative content analysis of peer-reviewed studies indexed in Scopus (2020–2025), this paper examines how digital CSR communication channels, transparency, and civic engagement mediate corporate-society relationships. Findings reveal that companies that integrate transparent, digitally mediated CSR communication significantly enhance public trust and generate sustainable social impact across local communities. The study further identifies key communication challenges including digital literacy disparities, cultural variation in CSR perception, and the gap between CSR disclosure and actual community outcomes. This paper contributes to the broader discourse on corporate communication, civic engagement, and digital culture in Southeast Asia, with implications for policy, practice, and academic inquiry.